Monitoring and Control System for Heat Experimental Equipment of High-Speed Vertical Spindle Bearings - Giang-Nam, Le; Xuan-Hieu, Ngo; Dinh-Quy, Pham; Vinh-Hai, Nguyen (Smart Systems and Devices, 2021)
High speed of spindle for high-speed machining is the mission and development trend of today’s machine tools. However, improper lubrication can cause a large temperature difference on the bearings, causing thermal deformation that affects the accuracy of the spindle. Heat experimental equipment for high-speed vertical spindle bearing is necessary. This paper presents a design and manufacture of control and monitoring system of heat experimental equipment for high-speed vertical spindle bearing based on PLC, WinCC and Webserver. This experimental device with supervisory control solution allows easy implementation of the test mode and data collection to plan out the appropriate lubrication mode. The system includes motor control and monitoring, observing of sensors, alarm and reporting at local and on site remotely. This solution can be applied to other industrial equipment to meet the needs of Industry 4.0.